Field notes contributed by Douglas C. Harr, May 28, 1996 - Harr, Douglas C.et al (1996)
Spring report of birds found in northwest Iowa contributed by Douglas C. Harr. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed